(untitled) (Swiss Medical Weekly, 2021)
BACKGROUND During the last 20 years, treatment for chronic lymphocytic leukaemia (CLL) / small lymphocytic lymphoma (SLL) has advanced, with improved clinical outcomes in randomised controlled trials. Currently, no data have been published from Switzerland to assess effectiveness of recent healthcare advances in CLL/SLL on a population-based level. We aimed to estimate trends in incidence, mortality and survival for patients with CLL/SLL in Switzerland. METHODS We retrospectively studied registry data from the National Agency for Cancer Registration (NACR) database in Switzerland from 1997 to 2016. We investigated incidence, mortality and survival in consecutive 5-year periods. Age-specific rates were calculated for three age groups (<65 years, 65–74 years and ≥75 years). RESULTS We obtained 6301 cases with CLL/SLL. Median age at diagnosis was 72 years. From 7.0 per 100,000 person-years in 1997–2002, age-adjusted incidence rates peaked at 7.8 per 100,000 person-years in the second time period, 2002–2006, and declined afterwards to 6.4 per 100,000 person-years in 2012–2016. Mortality declined from 2.4 per 100,000 person-years in 1997–2002 to 2.0 per 100,000 in 2012–2016. Five- and 10-year age-standardised relative survival increased from 77.9% and 55.6%, respectively, in 1997–2001 to 83.6% (p = 0.009) and 64.2% (p = 0.005), respectively, in 2012–2016. Improvement in age-specific relative survival was only significant in the middle age group (65–74 years). Incidence and mortality were significantly higher in males. Females had better relative survival. CONCLUSION We found no clear down- or upward trend in age-adjusted incidence rates. Age-standardised survival improved over time, mainly in the two younger age-groups, but this improvement was statistically significant in those aged 65–74 years only. Males have higher incidence rates, higher mortality and shorter survival than females. Reporting delay and underreporting are major limitations in the interpretation of registry data from patients diagnosed with CLL/SLL.